NILAI KERUKUNAN DAN KEKELUARGAAN ETNIS JAWA DALAM TRADISI AMONG-AMONG (Studi Pada Etnis Jawa Di Desa Magelang Kecamatan Kerkap Kabupaten Bengkulu Utara) - Yatiman Yatiman; Anis Endang SM; Sri Narti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
The tradition among all is a Javanese tradition carried out to commemorate the birthday of someone in the Javanese calendar. One of the Javanese who still carries out the traditions among the Javanese is in Magelang Village, Kerkap District, North Bengkulu Regency. This study aims to examine the value of harmony and family values ​​of ethnic Javanese in the tradition of among those in the village of Magelang. The method of this research is qualitative research using Roland Barthes's semiotic analysis. Determination of informants in this study was purposive sampling and data collection using observation, in-depth interviews and documentation. Based on the results of the study, it can be seen that Charcoal (symbolizing the furnace in the kitchen), money (all human needs purchased with money), rice (indicating cooked food), banana leaves (as a base for eating), red porridge (symbolizing maternal blood), porridge white (symbolizing father's sperm cells), fern leaves (as traditional medicine), dadap leaves (as traditional medicine when children are sick), eggs (as the center in ngepong emong), and urap (symbolizing ancient simplicity), while developing myths about the tradition of among the people is that this tradition is carried out to ask for the safety of the child to avoid being disturbed by supernatural beings. The value of harmony and family values ​​of Javanese ethnic in Magelang Village are maintained and intertwined with the implementation of these traditions. The community still adheres to the philosophy